Defect-engineering a metal–organic framework for CO2 fixation in the synthesis of bioactive oxazolidinones. Issue 19 (25th August 2020) - Helal, Aasif; Cordova, Kyle E.; Arafat, Md. Eyasin; Usman, Muhammad; Yamani, Zain H.
Abstract : Three-component, solvent-free cycloaddition of epoxides with aromatic amines and CO2 . Abstract : A novel series of UiO-66 structures with linker-induced defects was synthesized and fully characterized. By using a linker functionalized with a free, dangling alkylamine that replaces the ordinary carboxylate coordinating group, up to 40% of the linkers incorporated within the UiO-66 framework were defect sites. The resulting UiO-66 with linker-induced defects was then demonstrated to be a highly active heterogeneous catalyst. When applied to three-component, solvent-free cycloadditions of epoxides with aromatic amines and CO2 at ambient pressure, a diverse range of bioactive oxazolidinone compounds were isolated in significantly high yields (>90%) with quantitative conversions and regioselectivity. Finally, the catalyst was proven recyclable over 5 consecutive reactions without loss of performance.